2017
DOI: 10.1137/17m1124644
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Balance via Adiabatic Invariance of Approximate Slow Manifolds

Abstract: Abstract. We analyze the method of optimal balance which was introduced by Viúdez and Dritschel (J. Fluid Mech. 521, 2004, pp. 343-352) to provide balanced initializations for two-dimensional and three-dimensional geophysical flows, here in the simpler context of a finite dimensional Hamiltonian two-scale system with strong gyroscopic forces. It is well known that when the potential is analytic, such systems have an approximate slow manifold that is defined up to terms that are exponentially small with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Optimal balance is implemented by multiplying all nonlinear terms with a smooth monotonic 'ramp function' ρ(τ/T), where ρ : [0, 1] → [0, 1] with ρ(0) = 0 and ρ(1) = 1. Further, a sufficient number of derivatives of ρ need to vanish at the temporal endpoints; Gottwald et al (2017) give a rigorous analysis of why this is so. In this study, we use as ramp function…”
Section: Optimal Balance In Primitive Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal balance is implemented by multiplying all nonlinear terms with a smooth monotonic 'ramp function' ρ(τ/T), where ρ : [0, 1] → [0, 1] with ρ(0) = 0 and ρ(1) = 1. Further, a sufficient number of derivatives of ρ need to vanish at the temporal endpoints; Gottwald et al (2017) give a rigorous analysis of why this is so. In this study, we use as ramp function…”
Section: Optimal Balance In Primitive Variablesmentioning
confidence: 99%
“…Further, a sufficient number of derivatives of need to vanish at the temporal endpoints; Gottwald et al. (2017) give a rigorous analysis of why this is so. In this study, we use as ramp function which was shown to yield asymptotically the best performance in Masur & Oliver (2020).…”
Section: Nonlinear High-order Balancementioning
confidence: 99%
See 1 more Smart Citation
“…We refer the reader to [10,15] for the case of the Klein-Gordon equation and to Date: August 13, 2020. [9,12,13] for the case of system (2). Numerically, equation ( 1) is extensively studied in the relativistic regime [11,18].…”
Section: Introductionmentioning
confidence: 99%